Laboratorium Virtual Fisika dalam Pembelajaran Inklusif dan Implikasinya Terhadap Keterampilan Proses Sains Peserta Didik: Literature Review - Ramadhani, Aqirully; Rahmah, Baiq Ziadatu; Rizkika, Alya (Indonesian Publication Center, 2024)
Advances in physics education have spurred the use of virtual laboratories as an alternative and complementary option to conventional laboratories, particularly in the context of inclusive education. This study aims to examine the implementation of virtual physics laboratories, their role in supporting inclusive education, and their implications for students’ science process skills. The method used was a Systematic Literature Review (SLR) of 15 relevant scientific articles published between 2015 and 2024. The findings indicate that virtual laboratories can enhance science process skills through interactive and flexible experimental activities. Additionally, virtual laboratories support inclusive learning by providing flexible and adaptive learning access for students with diverse learning needs. The implementation of virtual laboratories also impacts students’ motivation, independence, and active participation in physics learning. However, the effectiveness of virtual laboratory implementation is significantly influenced by teacher readiness, the availability of technological infrastructure, and learning designs oriented toward scientific activities. Thus, virtual physics laboratories have the potential to serve as an inclusive and effective learning solution for developing students’ science process skills.